Dois ensaios sobre aspectos da instabilidade financeira - Salles, João Antônio Domingues de (2014)
This master thesis presents two papers devoted to Minsky s theory of financial instability. Studies have as starting point LIMA and MEIRELLES (2007). The objective is to develop a macrodynamic model where the following points are considered: the indebtedness influence on bank interest rate, the liquidity trap phenomenon, and the cyclical nature of economic fragility. In the first paper, LIMA and MEIRELLES (2007) and other related models are presented, intending to discuss the dynamics arising from bank interest rate and indebtedness. The new dynamics is based on Lotka-Volterra equations, with the sensivity of the interest rate regarding to indebtedness of the economy there included. The interest rate performs the role of the prey in Lotka-Volterra model, while the variable indebtedness acts as predator. The adopted structure for the new dynamics results in a cyclical behavior of the variables, thus promoting a fundamental change in the model and ensuring the achievement of the paper s objectives. The second paper runs simulations according the new dynamics. Economies chosen for the simulations were: United States, Spain, Brazil and the European Union. Parameters construction was based on January-November 2006 data for these economies. Results showed a cyclical nature of economies supporting theoretical correspondence with the model previously developed in the first paper, within workable intervals in the analyzed economies, corroborating subsequently observed trajectories, in addition.